Evaluating the Effectiveness of the Self‐Administered Interview© for Witnesses with Autism Spectrum Disorder. Issue 5 (23rd July 2014) - Maras, Katie L.; Mulcahy, Sue; Memon, Amina; Picariello, Federica; Bowler, Dermot M.
Summary The widely used evidence‐based police interviewing technique, the Cognitive Interview, is not effective for witnesses with autism spectrum disorder (ASD). The present study examined whether a modification of the Cognitive Interview that removes the social element, the Self‐Administered Interview©, is more useful in facilitating recall by ASD witnesses. One of the main components of the Cognitive Interview is context reinstatement, where the witness follows verbal instructions from the interviewer to mentally recreate the personal and physical context that they experienced during the event. The present findings showed that this procedure is not effective for witnesses with ASD in SAI format in which the social component of its administration is removed. However, the SAI sketch plan component did elicit more correct details from the ASD group, although to a lesser degree than for the comparison group. Theoretical and practical implications of the findings are discussed. Copyright © 2014 John Wiley & Sons, Ltd.